A Polyphenol-Based Multicomponent Nutraceutical in Dysmetabolism and Oxidative Stress: Results from a Pilot Study. (2nd January 2018) - Corsi, Roberto; Mosti, Giovanni; Cavezzi, Attilio; Urso, Simone Ugo; Dimitrova, Gayla; Fioroni, Elena; Colucci, Roberto; Quinzi, Valentina
ABSTRACT: To assess short-term efficacy and safety of a multicomponent nutraceutical (MCN) on dysmetabolism and oxidative stress, a pilot prospective observational study was performed on 21 individuals (12 men and 9 women) who took, for 60 days, 2 tablets per day of an MCN based on antioxidants and metabolism regulators: hydroxytyrosol (15 mg), maqui (300 mg), amla (200 mg), monacolin K (10 mg), berberine (245 mg), astaxanthin (0.5 mg), coenzyme Q10 (100 mg), and folic acid (200 mcg). On day 0 (T0) and day 60 (T60), all participants underwent laboratory tests related to lipid profile, carbohydrate metabolism, oxidative stress, and cellular inflammation. Statistical analysis was applied to the resulting data. A significant improvement of most atherogenesis and oxidative stress biomarkers was recorded (mean figure at T0 and T60, p value): total cholesterol 243.50/194.83 mg/dl, p =.0002; low-density lipoproteins 174.50/124.58 mg/dl, p =.0001; glycemia 96.25/88.50 mg/dl, p =.035; total free radicals 306.44/280.93 U.Carr., p =.036; serum antioxidant capacity 2103.00/2246.06 umol/l, p =.0042; oxidized cholesterol 680.33/597.25 uEq/l, p =.0511. Insulinemia, microalbuminuria, high-density lipoproteins, C-reactive protein, and triglycerides had no statistically significant variation. Body weight and systo-diastolic pressure showed no significant change from T0 to T60. No relevant side effects were reported. The investigated MCN (Eonlipid), based on polyphenols, significantly improved the oxidative stress parameters and decreased the majority of atherogenesis parameters at short term. No significant side effects were reported. Further placebo-controlled studies should possibly corroborate the promising results of this pilot study.